Análise de expressão diferencial entre estágios de desenvolvimento de Mahanarva Spectabilis (hemiptera) para prospecção de genes alvos no controle mediado por RNAi - Gonçalves, Gustavo Fernando Ferreira (Universidade Federal de São Carlos, 2025)
The pasture leafhopper Mahanarva spectabilis (Distant, 1909) is considered a key pest of pastures, as it sucks sap from the xylem and can lead to losses of up to 20% in biomass production in grasses. Resistance to these attacks is a desirable characteristic in any forage cultivar to be launched in Brazil, in addition to other large grasses (such as sugar cane) which are also affected. The search for ecologically sustainable ways to manage insect pests involves the use of molecular tools such as RNA interference (RNAi). This mechanism is used as a method of inducing resistance which has the advantages of greater target specificity, greater control efficiency and less impact on the ecosystem. In order to develop biodefense products using RNAi technology, certain steps are important, such as finding candidate target genes to be silenced so that the dsRNA (double-stranded RNA) developed does not find targets in cultivated plants or in non-target organisms (“off targets”). In addition, the target genes need to be involved in physiological processes that are critical for the insect's survival, so that when they are silenced they generate a preferentially lethal phenotype. In this study we reassembled the transcriptome of M. spectabilis from egg, nymph and adult samples, investigated the existence of the RNAi mechanism in the organism and prospected for target genes to be silenced. The transcriptome obtained was considered adequate in terms of size and representation of the RNAs provided, with 197,003 contigs, 25,492 of them (12.94%) with positive annotation in Blast, an average size of 364 bp per contig, N50 of 853 bp and 34.48% GC content. The results reveal the high number of transcripts referring to essential components in the RNAi response found in the transcriptome (such as Dicer 1-2, Argonauta 1-2-3, Piwi, Spindle, Gawky, Armi, among others), indicating the feasibility of using this tool to control the insect. Gene expression analysis categorized 10,928 contigs (5.54%) present in the transcriptome as DEGs, with the comparisons of eggs with adults being the most distinct and small nymphs with large nymphs being the most similar. In addition, from the function and expression analysis, five genes involved in different key stages of insect survival and with high expression (V-ATPase, trehalase, calmodulin, apolipoprotein D and hexokinase type 2) were selected as possible targets for a dsRNA that would direct efficient and specialized silencing.
Differential expression analysis between developmental stages of Mahanarva Spectabilis (hemiptera) to prospect for target genes in RNAi-mediated control
Keywords: Cigarrinha-das-pastagens; Transcriptoma; Bioinformática; RNAi; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL